2020
DOI: 10.1007/978-3-030-50309-3_21
|View full text |Cite
|
Sign up to set email alerts
|

“Alexa, Are You Spying on Me?”: Exploring the Effect of User Experience on the Security and Privacy of Smart Speaker Users

Abstract: Smart speakers are useful and convenient, but they are associated with numerous security and privacy threats. We conducted thirteen interviews with users of smart speakers to explore the effect of user experience (UX) factors on security and privacy. We analyzed the data using Grounded Theory and validated our results with a qualitative meta-synthesis. We found that smart speaker users lack privacy concerns towards smart speakers, which prompts them to trade their privacy for convenience. However, various trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…However, these studies do not take an overarching view of how these themes may interact, leading to a potential disconnect between these areas. A number of studies concentrated on user behaviour, identifying privacy and security concerns; however, they did not mention how these concerns might be addressed, except [ 33 ], in which a few suggestions were provided for privacy and security design, including improvements to muting, privacy default settings, and audio log features, as well as adding security layers to voice recognition and providing offline capabilities. In addition, it was found that when one particular VA was the focus of the study, Amazon’s Alexa was the assistant that was chosen in the majority of these papers.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies do not take an overarching view of how these themes may interact, leading to a potential disconnect between these areas. A number of studies concentrated on user behaviour, identifying privacy and security concerns; however, they did not mention how these concerns might be addressed, except [ 33 ], in which a few suggestions were provided for privacy and security design, including improvements to muting, privacy default settings, and audio log features, as well as adding security layers to voice recognition and providing offline capabilities. In addition, it was found that when one particular VA was the focus of the study, Amazon’s Alexa was the assistant that was chosen in the majority of these papers.…”
Section: Discussionmentioning
confidence: 99%
“…Lau et al [103] conducted a diary study with 34 smart speaker user and non-users, to find that smart speaker users lacked knowledge on privacy risks whereas non-users lacked trust on the vendors. This was further highlighted by Malkin et al [113] and Chalhoub and Flechais [42], who commented on how users preferred comfort to privacy because of the low level of privacy concern and any desire to observe privacy behaviors is inhibited by the lack of user-friendly interface. Concerns about the privacy risks that smart speakers can track and listen to users' data were observed in two studies [46,85].…”
Section: Periodmentioning
confidence: 99%
“…Crabtree et al [49] studied digital practices of 20 homes in the UK and found that participants employs a number of 'fine-grained methods'(throwaway emails, ad blockers, cookies, consent forms, private browsing) to manage the flow of their private data securely. Chalhoub and Flechais [42] investigated home users' attitude in terms of the user experience (UX), and pointed out that the lack of users' privacy concerns arose out of their individual perception of the situation and how they traded their privacy needs for the benefits from smart devices. Lau et al [103] and Malkin et al [113] found no evidence of privacy-seeking behaviors in users of smart speakers, and observed that users did not use privacy controls already available to them in such devices.…”
Section: Rq5mentioning
confidence: 99%
“…Another research that aims to examine how users perceive the security and privacy of voice assistants was conducted by Chalhoub and Flechais [62]. In this research, data collected from 13 people through interviews, lead to the conclusion that people are not worried about sharing their personal data because they have nothing to hide.…”
Section: Voice Assistants' Privacy and Securitymentioning
confidence: 99%